2012
DOI: 10.1111/j.1551-2916.2012.05140.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chitosan/Boron Nitride Composites

Abstract: Chitosan/Boron nitride (BN) composites were prepared by solution method using CuSO4/glycine chelate complex as the catalysis with variable percentage of boron nitride loading. The dispersion of BN with the chitosan polymer was achieved with sonication at power of 120 W and frequency of 80 kHz. The chemical interactions of chitosan and BN were studied by Fourier transform infrared spectroscopy. The structure of chitosan and BN composites were investigated by XRD and TEM. It was observed that the BN were dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 28 publications
(40 reference statements)
2
42
0
Order By: Relevance
“…Albumin=SiC nanobiocomposites were prepared by a solution method using CuSO 4 =glycine chelate complex as per our earlier method [28] with different percentages of silicon carbide. A 1% (w=v) stock solution of albumin bovine was prepared in double-distilled water.…”
Section: Preparation Of Albumin Bovine/sic Nanobiocompositesmentioning
confidence: 99%
“…Albumin=SiC nanobiocomposites were prepared by a solution method using CuSO 4 =glycine chelate complex as per our earlier method [28] with different percentages of silicon carbide. A 1% (w=v) stock solution of albumin bovine was prepared in double-distilled water.…”
Section: Preparation Of Albumin Bovine/sic Nanobiocompositesmentioning
confidence: 99%
“…38,[43][44][45] One of the most important applications of 2D fillers in polymer-based composites are as barrier materials to reduce the permeability of the material to gases. 53 Recently, it has been reported that solution processing can be used to mix h-BN with a range of materials, including gelatin, cellulose, chitosan and soy protein, [54][55][56][57] resulting in improvements in their barrier properties. 46 Due to their low cost, high aspect ratio and low toxicity, nanoclays have been well-studied as barrier-enhancing fillers for polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] For instance, the hBN has its analogue in graphite; it is white, insulating, soft, and lubricating. There are four known different modifications, cubic boron nitride (cBN), wurtzite boron nitride (wBN), hexagonal boron nitride (hBN), and rhombohedral boron nitride (rBN).…”
Section: Introductionmentioning
confidence: 99%
“…The hBN and rBN have layered structures with lower density than cBN and wBN. [1][2][3][4][5][6] For instance, the hBN has its analogue in graphite; it is white, insulating, soft, and lubricating. It has a density comparable to graphite and a high degree of anisotropy; for example, the conductivity in the "a" direction is higher than in the "c" direction by a factor of about 20.…”
Section: Introductionmentioning
confidence: 99%